2018
DOI: 10.1021/acs.jpclett.8b01360
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Photomorphic Reaction Dynamics of Plasmonic Nanoparticles in Liquid by Four-Dimensional Electron Microscopy

Abstract: Liquid-cell electron microscopy (LC-EM) provides a unique approach for in-situ imaging morphology change of nanocrystals in liquids under electron beam irradiation. However, nanoscale real-time imaging of chemical/physical reaction processes in liquids under optical stimulus is still challenging. Here, we report direct observation of photomorphic reaction dynamics of gold nanoparticles (AuNPs) in water by liquid-cell four-dimensional electron microscopy (4D-EM) with high spatiotemporal resolution. The photoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…It has been demonstrated that, because of the resonant surface plasmon excitation enhanced optical absorption and thus the strong photothermal effect, , repetitive femtosecond laser pulse excitation on gold NPs in water results in randomly rapid nucleation, expansion, and collapse/detachment of plasmonic NBs around the NP surface, which could generate random driving forces and propel the NP diffusion. , This mechanism is further verified by transient creation of a plasmonic bubble around a gold NP cluster and subsequent ejected motion of the cluster captured by our single-pulse imaging experiment, which will be discussed later. In our experiment, because of the capillary flow drag due to the different vapor rate at the curved surface or the meniscus effect , arising from the liquid surface tension, the gold NP is strongly constrained at the liquid–gas interface (see Figure S1a and b) and thus can only move along the interface under the plasmonic NB propulsion.…”
Section: Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been demonstrated that, because of the resonant surface plasmon excitation enhanced optical absorption and thus the strong photothermal effect, , repetitive femtosecond laser pulse excitation on gold NPs in water results in randomly rapid nucleation, expansion, and collapse/detachment of plasmonic NBs around the NP surface, which could generate random driving forces and propel the NP diffusion. , This mechanism is further verified by transient creation of a plasmonic bubble around a gold NP cluster and subsequent ejected motion of the cluster captured by our single-pulse imaging experiment, which will be discussed later. In our experiment, because of the capillary flow drag due to the different vapor rate at the curved surface or the meniscus effect , arising from the liquid surface tension, the gold NP is strongly constrained at the liquid–gas interface (see Figure S1a and b) and thus can only move along the interface under the plasmonic NB propulsion.…”
Section: Results and Discussionsupporting
confidence: 59%
“…e ., single-pulse imaging mode, where the time delay between the nanosecond electron pulse and the femtosecond laser pulse was precisely controlled by a digital delay generator and the temporal resolution was not affected by the response time of the charge-coupled device (CCD). Details of the imaging procedures have been also reported in our previous studies. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…In some cases, if metallic nanoparticles are crystallized, single crystal X-ray methods can be used to determine their structures, or atomic resolution tomographic images of individual nanoparticles can be obtained. However, in general, additional methods for quantitative and rapid 3D atomic structural characterization of disordered nanomaterials are needed because traditional techniques such as powder X-ray diffraction (XRD), highresolution transmission electron microscopy (HRTEM), 7,8 Xray absorption ne structure (XAFS), 9,10 small-angle X-ray scattering (SAXS), 11,12 grazing incident small-angle X-ray scattering (GISAXS), 13,14 differential scanning calorimetry (DSC), 15,16 and others, are well suited to bulk-like crystalline materials for the determination of phase behavior, particle size, and so on. XAFS techniques such as XANES and EXAFS have widely been used to probe the valence state and nearest-atomic neighbor arrangement, but they are not sensitive to the longer range atomic structure in nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…2 The dynamics of nanoparticles in liquids have been examined experimentally by four-dimensional electron microscopy. [9][10][11] In a recent article, 12 some of the authors have used femtosecond electron diffraction (FED) 13 to investigate ultrafast atomic motions of Au NCs on thin-films under nonequilibrium conditions. The observed dynamics of diffraction peaks could be explained in terms of energy flow between the electrons and the atomic vibrations of the NCs and the substrate.…”
Section: Introductionmentioning
confidence: 99%